Development of Multi Micro Holes Synchronous Rotating and Vibration EDM Machine Tool. Issue 4 (March 2020) - Mao, Xiaowen; Yang, Xuguang; Zhang, Mingfang; Zhu, Zhenjie; Huo, Mengyou
Abstract: In order to solve the problem of low efficiency of single electrode discharge machining, complex process and limited machining quality of group electrode array hole machining technology in traditional micro EDM machine tools, a multi-micro-hole synchronous rotating and vibration EDM machine tool was developed. The machine tool is composed of a mechanical platform and a control system. It can realize multi-electrode independent micro-energy pulse discharge, real-time detection of each electrode gap state and servo feed adjustment, and synchronous rotation assisted vibration of each electrode. The mechanical platform of the machine tool consists of servo feed mechanism, vibrating mechanism and multi-electrode synchronous rotating mechanism. The structure optimization and stability analysis are carried out by ANSYS finite element analysis software to ensure that the design of each part of the machine tool is reasonable and reliable. The control system is composed of motor control module, servo motion control module and pulse power module. It uses STM32F103RCT6 MCU to detect the machining state in real time and coordinate the work of each module, and uploading the processing data to upper computer. The Experimental tests show that the machine tool has high machining efficiency, stability and precision, and high degree of automation.